Pengaruh Pendidikan Jasmani terhadap Perilaku Hidup Bersih dan Sehat pada Siswa di Sekolah Dasar Negeri Sidorejo - Dwi Hapsari; Ribut Wahidi; Suharningsih Suharningsih (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. This study aims to determine the effect of Physical Education, Sports, and Health (PJOK) learning on the clean and healthy lifestyle behaviour (PHBS) of sixth-grade students at Sidorejo State Elementary School in Pekalongan Regency. Materials and methods. This study used a mixed methods approach with a sequential exploratory design. The study population consisted of all 180 students at Sidorejo State Elementary School, with a sample of 30 sixth-grade students selected using purposive sampling. Data were collected using PJOK and PHBS learning questionnaires and analysed using validity, reliability, normality, and Product Moment correlation tests with the assistance of SPSS 25. Results. The results showed that all items in the instrument were valid and reliable with a moderate category. The data were normally distributed, and the correlation test results showed a value of r = 0.682 with a significance of 0.032 (p < 0.05), which means that there is a strong influence between PJOK learning and students' clean and healthy lifestyle behaviours. Conclusion. PJOK learning not only plays a role in increasing physical activity, but is also effective in fostering awareness and habits of clean and healthy living among primary school students.